Investigation of the joining characteristics of Al-B4C composites manufactured by friction welding - Orhan, Ayhan (Walter de Gruyter Gmbh, 2015)
In this study, metal matrix composite materials consisting of 99% pure Al powder as the matrix and 99% pure B4C powder as the reinforcement were manufactured by the powder metallurgy method. The main objective of this study was to investigate the effects of process parameters on the microstructural and mechanical properties of an Al/B4C metal matrix composite fabricated by using the friction welding technique. An aluminum-based metal matrix composite material containing 20 vol% B4C particles with an average particle size of 30 mu m was manufactured by hot isostatic pressing processing. While the joining characteristics of the friction welded joints were investigated by optical and scanning electron microscopy, the mechanical properties were assessed with microhardness and shear tests. According to the results of microstructure analyses and mechanical test, it was obvious that welding properties, such as microstructure and strength, were strongly affected by rotational speed and friction time.
Keywords: Al/B4C; friction welding; microhardness; microstructure; shear-lap test